Application of Statistical Methods in Education Sciences: the Didactical Principles in the Educational Means Prepared by Bronislovas Bitinas - Pečiuliauskienė, Palmira (Pedagogika, 2016)
Based on works of professor B. Bitinas this article analyses educational materials on applying statistical methods in education sciences. The educational materials on applying statistical methods in education sciences can be classified into two groups: methodological group (the application of mathematical statistics in quantitative research) and technological group (computer software for processing quantitative research data). The article analyses application of didactical principles in the methodological group and the technological group. Didactical principles provide direction for learning process and govern contents, methods and organisation of learning. Different didactical principles can be used when preparing educational materials on the applying statistical methods in education as principle of the availability and principle of relation between the theory and practise. Application of statistical methods in education sciences is influenced by technological tools used for processing statistical data. These tools changed from electronic calculating machines (ECM) to modern computers with modern statistical programs. Technological change influences didactical principles applied for preparing educational materials on applying statistical methods in education sciences. The comparative analysis of learning materials on applying statistical methods in education sciences prepared by Professor B. Bitinas shows that the principle of availability was an important principle at the time of the processing statistical data using the ECM. This principle is less important when statistical data is processed using modern statistical computer programs. Didactical principle of the relation between theory and practice was important in the early (the eighth-ninth decade of XX century) and later stages (the twentyfirst century.) Professor B. Bitinas prepared both methodological (the usage of mathematical statistics into quantitative research) and technological (computer software for quantitative research data processing) learning means. The didactical principles in the methodological and technological learning means are different. The principle of the availability and the principle of relation between the theory and practise dominate in the methodological learning means. The principle of systematization and continuity is important in technological learning means.